2018
DOI: 10.1093/jas/sky221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal nutrition and rumen-protected arginine supplementation on ewe performance and postnatal lamb growth and internal organ mass1

Abstract: The hypothesis of this study was that arginine supplementation would overcome negative effects of restricted maternal feed intake during the last two-thirds of gestation on ewe performance and positively affect postnatal lamb growth and development. Multiparous, Rambouillet ewes (n = 32) were allocated to 3 treatments in a completely random design at 54 ± 3.9 d of gestation. Dietary treatments were 100% of nutrient requirements (control, CON), 60% of control (restricted, RES), or RES plus a rumen-protected arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…Data were extracted on fetal growth in response to prenatal supplementation of arginine family AA from 47 animal studies (1 mouse [ 33 ], 18 rat [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], 6 sheep [ 52 , 53 , 54 , 55 , 56 , 57 ], 20 pig [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ], and 12 human studies [ 78 , 79 , 80 , 81 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were extracted on fetal growth in response to prenatal supplementation of arginine family AA from 47 animal studies (1 mouse [ 33 ], 18 rat [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], 6 sheep [ 52 , 53 , 54 , 55 , 56 , 57 ], 20 pig [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ], and 12 human studies [ 78 , 79 , 80 , 81 ,…”
Section: Resultsmentioning
confidence: 99%
“…Effect of Prenatal AA in Arginine Family on Maternal Weight Gain and Blood Glucose Levels Gestational weight gain was reported in 23 animal studies (1 mouse [ 33 ], 10 rat [ 36 , 37 , 43 , 44 , 45 , 46 , 49 , 90 , 91 , 148 ], 3 sheep [ 53 , 54 , 55 ], and 9 pig/swine [ 58 , 59 , 66 , 67 , 69 , 74 , 75 , 76 , 149 ]) and only 1 human study (Poland) [ 95 ] ( Table A8 ). Again, the most studied amino acid was arginine ( n = 19) [ 33 , 36 , 37 , 44 , 45 , 46 , 49 , 53 , 54 , 55 , 58 , 59 , 69 , 74 , 75 , 76 , 90 , 91 , 95 ], but also glutamate ( n = 5) [ 54 , 55 , 66 ...…”
Section: Appendix A1 Expanded Methodsmentioning
confidence: 99%
“…Supplementing ruminally protected arginine to pregnant ewes fed either adequate or nutrient-restricted diets increased the growth trajectory of lambs ( Peine et al, 2013 , 2018 ). Lassala et al (2010 , 2011 ) reported that intravenous administration of l -arginine in nutrient-restricted ewes from day 60 until parturition, or in triplet- and quadruplet-bearing ewes from days 100 to 121 of gestation increased birth weights of lambs.…”
Section: Maternal Nutrition and Developmental Programmingmentioning
confidence: 99%
“…Maternal nutrition of L-arginine (L-Arg), a semiessential amino acid, and its precursor N-carbamylglutamate (NCG) during pregnancy has been shown to mitigate the IUGRmetabolic disruptions in ovine fetus [18][19][20][21] and rat offspring [22] and enhance fetal development and neonatal survival and growth in mammals [23][24][25]. Also, L-Arg and NCG have been shown to protect the liver against lipid peroxidation [26][27][28] as well as play a key role in inflammatory response regulation [29].…”
Section: Introductionmentioning
confidence: 99%